Pembelajaran Kontekstual untuk Membentuk Perilaku Berwawasan Lingkungan Siswa Sekolah Menengah Kejuruan - - Sudarman (Universitas Negeri Malang, 2013)
Abstract: Contextual Teaching and Learning Strategy to Develop Environmentally-Oriented Behaviors of Vocational High School Students. This study aims at investigating the effectiveness of CTL using Science Environment Technology and Society (SETS) orientation in developing environmentally-oriented behaviors of vocational high school students joining on-the-job training. Using research and development design, this study involved 36 students. The data collected from tests and observation were descriptively analyzed. The results show that students taking on-the-job training need to be equipped with theoretical knowledge of environmentally-oriented behaviors prior to the training as well as practical knowledge of how to test exhaust emissions, how to test water, and how to produce compost. At the end of the study, the students also reflect  better behaviors and learning achievement. Abstak: Strategi Pembelajaran Kontekstual untuk Membentuk Perilaku Berwawasan Lingkungan Siswa Sekolah Menengah Kejuruan. Penelitian ini bertujuan mengetahui efektifitas strategi pembelajaran kontekstual berwawasan Science Environment Technology and Society (SETS) dalam pembentukan perilaku berwawasan lingkungan peserta Praktik Kerja Industri (Prakerin). Penelitian dan pengembangan ini dilakukan di SMK Teknik Mekanik Otomotif dan industri di kota Semarang tahun 2010 dengan sampel 36 siswa. Data dikumpulkan dengan tes, observasi dan dianalisis secara deskriptif dan regresi linear, Penelitian menemukan bahwa untuk membentuk perilaku berwawasan lingkungan, pembelajaran Pendidikan Lingkungan Hidup (PLH) dilakukan pada pembekalan Prakerin. Di samping di kelas, siswa juga melakukan praktik pengujian emisi gas buang, pengujian air dan pembuatan kompos. Perilaku berwawasan lingkungan dan hasil belajar PLH para siswa sebagian besar tinggi.